Two faces of collaboration: a critical perspective on effects of collaboration in learners' corpus consultation - Hyeyoung Cho, (Penerbit UKM, 2015)
Collaborative learning has been increasingly incorporated into learners' corpus consultation as a type of pedagogic mediation. However, studies found that collaborative learning has negative aspects as it may cause conflicts and power inequality among members. Given the two sides of collaboration, this study provides a critical investigation on the functions of collaboration in learners' corpus consultation. Through two collaborative corpus analysis sessions, three students of different L2 proficiency levels assisted each other’s understanding of corpus data to complete group activities. The students’ verbal and nonverbal behaviors during corpus analysis became the main source of investigation, complemented by the results of pre-/post-interviews and the researcher's direct observations. The findings of this study suggest that collaboration creates significant power inequality among the participants by gradually marginalizing the less capable student in the group from the learning process and increasing the psychological burden for the most capable student. In addition, collaborative work during corpus consultation could impede critical learning opportunities for individual students to pursue personal queries during collaboration. Despite some limitations, the findings of this study provide a realistic picture of collaboration in learners’ corpus consultation and suggest pedagogical implications to corpus-based instruction.